Model Penguatan Dakwah dalam Persaingan Politik Islam di Malaysia - Daulay, Hamdan (At-Tabayyuun: Journal Islamic Studies, 2019)
Mahathir Mohammad even succeeded in embracing Anwar Ibrahim as part of the government, while at that time Anwar was known as an important figure of ABIM known for the harsh criticisms towards the government. The presence of Anwar Ibrahim as a Muslim figure in the government circle made the policies of Islam politics more real and stronger, although Anwar Ibrahim was eventually dumped by Mahathir due to the dynamics of the politics happening in Malaysia. Irrespective of the political conflicts that occurred between Mahathir Mohammad and Anwar Ibrahim, it was undeniable that there were quite a number of policies benefitting the Muslims and Malay ethnic during this period. Among other benefits were the establishing of Islam banks, Islam insurance, International Islamic Universities, up to a huge support given by the royal family to propagate Islam from the scale of the village to a national one. Malaysia is actually a multi-ethnic and multi-faith society. The Malays only slightly outnumber half of the population, but they dominate the power of politics and culture. The rest are comprised of various ethnics such as Chinese and Indian. Islam and national identity together with the Malay politics have long beeiyntertwined, mirrored in the common belief that a Malay must be a Muslim.